Impact resistance performance of diamond film on a curved molybdenum substrate. (3rd August 2017) - Chen, Yang; Gou, Li
Abstract: Diamond films with different thicknesses were deposited on flat and curved molybdenum substrate by the microwave plasma chemical vapour deposition (MPCVD) method. Scanning electronic microscopy, atomic force microscopy and Raman spectroscopy were employed to characterise the morphology, the surface roughness and the composition of the films, respectively. A NanoTest system was used for hardness, elastic modulus and nanoimpact tests. The curved surface and ductility of the molybdenum substrate allow large deformation for the thinner films. The substrate has less effect on impact for the thicker film, the deformation of which is mainly determined by the film composition. Under a load of 50 mN and 75 cycles, less deformation occurred for the 22 μm thick film on the curved molybdenum substrate.